Menumbuhkan Budaya Hidup Bersih Siswa dengan Memanfaatkan Media Ecobrick di Sekolah Dasar - Duratussania, Firda Ditya; Halimatussa’diyah, Della; Alpian, Yayan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Ecobrick is one of the creative ways to manage plastic waste and turn it into useful objects, reducing pollution and toxins caused by plastic waste. The function of ecobrick is not to destroy plastic waste, but to extend the life of the plastics and process them into something useful, which can be used for the benefit of people in general. Ecobrick is a waste management technique made from used plastic bottles filled with clean plastic waste until full, then compacted until it becomes hard. After the bottles are full and hard, they can be assembled with glue. These assembled bottles can be turned into tables, simple chairs, building materials for walls, towers, small stages, and even potentially assembled into fences and foundations for simple playgrounds. The utilization of plastic waste at SDN Kondangjaya III is through the making of ecobricks. This activity is due to problems related to plastic waste, such as the abundance of waste in the school environment that has not been utilized, the presence of a specific plastic bottle waste bin in the school environment that is not being utilized, and the lack of understanding and knowledge in waste management to be utilized into something useful. From these various problems, it can be concluded that many elementary school students have not learned to recycle waste. The methods used are observation, demonstration, and direct practice in making ecobricks. The result of this activity is an increase in knowledge and understanding about the utilization of plastic waste and an improvement in the skills and creativity of students in managing plastic waste into useful objects.